THE SUSTAINABILITY OF THE INFRASTRUCTURE SYSTEM AT UNIVERSITI MALAYSIA SABAH IN GENERATING A CONDUCIVE LEARNING ENVIRONMENT - Mohd Nur Hidayat Hasbollah Hajimin,; Syamsul Azizul Marinsah,; Irma Wani Othman,; Mohd Sohaimi Esa2, (Journal of Islamic, Social, Economics and Development, 2021)
This paper discusses the visibility of infrastructure integration in the context ofsustainability of a conducive learning environment for international students at UMS in thepost Covid-19th millennium. The sustainability of a conducive learning environment processindicates the commitment of the university’s management in materialising the country’sinternationalisation policy. The concept of conducive environmental sustainability is centredon the vital functions and effectiveness of the infrastructure system implemented by auniversity. It has continuity with a system of well-being and welfare support which is anattractive factor in the selection of Malaysia as a study destination for international students.Ideally, the provision of a university infrastructure includes three components, (a) learningand teaching infrastructure, (b) Information Technology (IT) infrastructure, and (c) researchinfrastructure. This study has two main objectives, namely (1) to explore the views ofinternational students on the sustainability of the infrastructure system in UMS and (2) toevaluate the views of students on the responsibility of UMS in providing a conducive learningenvironment. A qualitative approach using in-depth interview techniques was selected basedon the background of an exploratory study. A total of 13 international students studying atUMS were interviewed online to obtain empirical data which allows the application ofthematic techniques to the transcription of such in-depth interviews through the process ofcoding dominant and subdominant themes. The discussion of this paper utilises a selection ofnarratives from study respondents that focuses on three dominant themes namely; (i) views ofinternational students on the sustainability of UMS infrastructure and physical environment,(ii) views of international students on psychosocial environment towards generating a conducive teaching and learning environment in UMS, (iii) the views of international studentson the efficiency of the service system of the Centre for Internationalisation and GlobalEngagement Universiti Malaysia Sabah (UMS).